Isolated fronto-ethmoidal allergic fungal rhinosinusitis: case report and review of the literature - Oretti, Gabriele; Castellana, Giuseppe; Manuguerra, Roberta; Silini, Enrico Maria; Ferri, Teore (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Fungal rhinosinusitis (FRS) is a clinical entity characterized by the presence of fungi within sino-nasal cavities that may occur in patients with normal or defective immunity. Allergic fungal rhinosinusitis (AFRS) is a form of non-invasive FRS that affects patients with an abnormal immuno-mediated response to fungal antigens. This article describes a case of isolated fronto-ethmoidal AFRS. Methods: A 20-year old male patient presented with a history of a left nasal respiratory obstruction and allergic oculorhinitis. CT scans showed a polypoid mass in the left nasal cavity and opacification of the left ethmoid sinus, frontal recess and frontal sinus with hyperdense component. The patient underwent functional endonasal sinus surgery (FESS) with removal of nasal polyps from the left nasal cavity and of cheesy-like material and dense mucus from the left ethmoid and frontal sinus. Histological examination showed presence of fungal hyphae within the allergic mucus; a diagnosis of AFRS was made. Results: Follow up at 14 months showed no signs of recurrence. Conclusions: The AFRS case reported herein is characterized by isolated unilateral fronto-ethmoid involvement, a rare presentation. Endoscopic nasal treatment was effective with complete patient recovery. (www.actabiomedica.it)